Identificações estéticas no sistema da moda: um olhar através dos sites de moda de rua e de festa - Pereira, Camila Konradt (Universidade do Vale do Rio dos Sinos, 2010)
The purpose of this research Project is to investigate the social relations established from the street style websites and blogs and other social environments that are related. Considering, in a first moment, that the relations produced in these environments, in fashion and in style way, can generate identifications that presents itself in a esthetic way and through speech. Therefore it is intended to analyze how bloggers and photographed people articulate the communication through speech and esthetic in the construction of identifications and how these can influence values, preferences and cultural manifestations in sense of style and fashion
Keywords: Identificações; Estética; Street style; Sites; Blogs; Identification; Esthetic; Websites; ACCNPQ::Ciências Humanas::Sociologia